The role of the S-O-R model in explaining impulsive buying in social commerce in Indonesia - Yutika, Fitri; Purnama, Doni (Jurnal Mantik, 2025)
The swift rise of social commerce in Indonesia, particularly through video-centric features like TikTok Shop and Shopee Video, has significantly transformed consumer behavior and increased impulsive buying. This study aims to examine how short video attractiveness and shopping convenience (stimuli) affect perceived usefulness (organism) and lead to impulsive buying (response) using the Stimulus-Organism-Response (S-O-R) framework. The research contributes by providing new insights into the psychological mechanisms that drive impulsive behavior in Indonesia's growing social commerce sector. A quantitative approach was applied, involving a survey of 101 social commerce users familiar with short video shopping cart features. Path analysis was used to test the proposed relationships. The results reveal that both short video attractiveness and shopping convenience significantly increase perceived usefulness. In turn, perceived usefulness strongly influences impulsive buying. Additionally, both stimuli were found to have direct effects on impulsive buying. Perceived usefulness acts as a partial mediator, explaining a meaningful portion of the influence of the stimuli on the buying response. These findings highlight that engaging content and seamless shopping experiences are key factors in encouraging impulsive behavior in Indonesia’s social commerce environment. This study offers practical guidance for marketers and platform designers aiming to boost consumer engagement and digital sales.